KEBIJAKAN PEMERINTAH DAERAH DALAM MENERTIBKAN PEREDARAN MINUMAN KERAS DI KOTA CILEGON PROVINSI BANTEN - Suwaib Amiruddin (Jurnal Hukum, 2012)
Product of local government is needed to regulate various aspects in a area, especially in regulating the distribution of alcohol. While, Cilegon a pluralistic society because it is a gateway island of Java-sumatera, so it takes the right product from the target governmentThe results showed that the city government is committed to eradicate Cilegon liquor circulation by issuing a Regional Regulation No. 5 of 2001 on Decency Abuse, Alcohol, Gambling, Drug Abuse, Psychotropic and other Addictive Substances. That rule is a reference in the discipline and control of liquor producers and consumers. Obstacles encountered in circulation curb liquor constrained in financing and the availability of human resources, especially law enforcement officers. In addition there are indications of the involvement of law enforcement in the enforcement practice of accepting money from producers and consumersKeywords: Policy, Alcohol, Local Regulation